Coexistence of multiple and widespread cardiovascular complications in a patient with Marfan syndrome. Issue 3 (27th March 2012) - Magnoni, Marco; Figini, Filippo; Piraino, Daniela; Cianflone, Domenico
Abstract Inherited connective tissue diseases such as Marfan syndrome are frequently associated with cardiovascular manifestations. Aortic involvement with dilation and dissection is the most common finding and the major cause of death in Marfan syndrome patients. We report the echocardiographic study of a 53‐year‐old male patient with uncommon coexistence of cardiovascular abnormalities typical of connective tissue disease at first clinical presentation in acute clinical setting: dissection of the descending aorta associated with severe mitral regurgitation due to leaflet flail and massive aortic insufficiency due to ascending aortic enlargement, leading to left ventricular dilation and dysfunction. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 2013